EDUCATION OF THE SPIRITUAL AND MORAL PERSONALITY OF STUDENTS THROUGH THE STUDY OF UZBEKISTAN FOLK MUSIC AND CULTURAL HERITAGE (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
This article discusses in detail the issues of educating the spiritual and moral personality of students through the study of Uzbek folk music and cultural heritage.